1998
DOI: 10.1021/om970997n
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Properties of {(Me3Si)2CH}2SnH(OH)

Abstract: The Lappert stannylene SnR2, R = CH(SiMe3)2, adds water and methanol to yield the low-melting-point, crystalline hydroxy- and methoxydiorganostannanes R2SnH(OH) (1) and R2SnH(OMe) (2). The corresponding deuterated derivatives R2SnD(OD) (1-d 2) and R2SnD(OCD3) (2-d 4) have also been prepared. Compounds 1 and 2 react with D2O with retention of the Sn−H bond to give R2SnH(OD) (1-d(SnOD)). The reaction is thought to proceed by an SN2 type mechanism via a [R2SnH(OR‘)2]- (R‘ = H, D, or Me) intermediate or transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
48
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 31 publications
3
48
0
Order By: Relevance
“…Interestingly,when the reaction is carried out at 70 8 8C, exchange of the phosphorus-bound hydride is also observed, providing a1:1 isotopic distribution. Therelative ease of H/D exchange is in agreement with aprevious report by Pçrschke et al [35] In addition to the previously observed doublet, attributable to the phosphorus center of 3,t he 31 PNMR spectrum of the reaction mixture also shows at riplet at d = À37.7 ppm ( 1 J P-D = 133 Hz). Acomplementary doublet is also Figure 3.…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly,when the reaction is carried out at 70 8 8C, exchange of the phosphorus-bound hydride is also observed, providing a1:1 isotopic distribution. Therelative ease of H/D exchange is in agreement with aprevious report by Pçrschke et al [35] In addition to the previously observed doublet, attributable to the phosphorus center of 3,t he 31 PNMR spectrum of the reaction mixture also shows at riplet at d = À37.7 ppm ( 1 J P-D = 133 Hz). Acomplementary doublet is also Figure 3.…”
Section: Methodssupporting
confidence: 92%
“…[23] Theo xidative activation of water is of immense current interest, representing ac rucial step in metal-catalyzed water splitting.D espite this fact, there are few transition-metal complexes that are able to effect this transformation. [2] Although there are several reports outlining similar reactivity at main group centers, [33][34][35][36][37][38][39][40][41] there are currently only two examples that are able to do so without the use of forcing conditions,n on-equimolar loadings of water, or secondary activating substrates. [37,41] Ther oom-temperature reaction of 3 with one equivalent of deuterium oxide results in exchange of the hydroxyl proton.…”
Section: Methodsmentioning
confidence: 99%
“…for several hours. This is substantiated by the fact that the hydroxo hydrido diorganostannane 13, [13] containing H 2 O in a ªpreactivatedº form, does not react with the monometallic organoiron compound 9 to give 12. However, chromatography on freshly dried Al 2 O 3 , containing virtually no water, leaves 10 unchanged, clearly indicating the high reactivity of the iron ± tin complex 10 towards nucleophilic attack by trace amounts of water.…”
Section: Resultsmentioning
confidence: 99%
“…The IR spectra (KBr) of 12 and 15 display n(SnÀOHÀSn) stretching vibrations at 3650 (12) and 3615 cm À1 (15). [13] The bands from the n(FeÀH) and n(CoÀH) stretching modes in 12 and 15 are unfortunately broad and thus ill-defined, making a reliable assignment impossible. These frequencies are in accord with the nSn À OH À Sn stretching frequencies of the Ni complex [(h 5 -Cp)Ni{(SiMe 3 ) 2 CH} 2 Sn(OH)Sn{CH(SiMe 3 ) 2 } 2 ] [11] (n(OH) 3621 cm À1 ) and the hydroxo organostannane complex 13 (n(OH) 3660 cm À1 ).…”
Section: Resultsmentioning
confidence: 99%
“…There are no published data on diorganylstannanols; obviously, such compounds are very unstable. Only when bulky trimethylsilyl groups were attached to tin, the hydrolysis of the corresponding tin(II) compound gave bis[bis(trimethylsilyl)methyl]stannanol [(Me 3 Si) 2 CH] 2 · SnH(OH) [12]. Diethylstannanol Et 2 SnH(OH) necessary as reference cannot be obtained by analogous procedure; according to published data, diethyltin is an oligomer [(C 2 H 5 ) 2 Sn] n [13,14], and it fails to react.…”
mentioning
confidence: 99%